Prenasal thickness to nasal bone length ratio in normal and trisomy 21 fetuses at 11–14 weeks of gestation. (4th August 2015) - Manegold‐Brauer, Gwendolin; Bourdil, Lucas; Berg, Christoph; Schoetzau, Andreas; Gembruch, Ulrich; Geipel, Annegret
Abstract : What's already known about this topic? The prenasal thickness (PT) to nasal bone length (NBL) ratio is a strong marker for trisomy 21 fetuses in the second trimester, and preliminary data from the first trimester in 9 fetuses with trisomy 21 showed an increased PT What does this study add? A reference range for PT/NBL ratio in 1000 normal fetuses compared to 44 fetuses with trisomy 21. A cut‐off value of 0.8 showed a sensitivity of 86.4% and a specificity of 98.4% for trisomy 21. PT/NBL between 11 and 14 gestational weeks is feasible with high intraclass correlation. © 2015 John Wiley & Sons, Ltd. Abstract: Objective: To show the feasibility and to create a reference range for prenasal thickness (PT) and for the PT to nasal bone length (NBL) ratio in normal fetuses at 11–14 gestational weeks and to compare the findings to fetuses with trisomy 21. Method: PT, NBL and PT/NBL ratio were measured retrospectively in stored two‐dimensional images of 1155 normal fetuses and 44 fetuses with trisomy 21. Mid‐sagittal images were acquired at first trimester ultrasound examinations and were selected from our digital database. Results: The PT increased with CRL from 1.0 mm at 45‐mm CRL to 1.6 mm at 84‐mm CRL. The mean PT/NBL ratio was 0.6 and was not altered by CRL. The mean PT/NBL ratio in fetuses with trisomy 21 was significantly higher than in normal fetuses ( p < 0.0001). For a cut‐off value of 0.8 the PT/NBL yielded a sensitivity of 86.4% and a specificity of 98.4% for trisomy 21. Conclusion: The assessment of PT between 11 and 14 gestational weeks is feasible with high intraclass correlation. The PT to NBL ratio seems to be a promising marker for trisomy 21 in the first trimester and was superior to the isolated contribution of NBL and PT measurements. © 2015 John Wiley & Sons, Ltd.